Effect of compatibilizer type on properties of 70:30 polyamide 6/polypropylene/MMT nanocomposites - Othman, Norhayani; Hassan, Azman; Rahmat, Abdul Razak; Wahit, Mat Uzir (2007)

(untitled)
PA6/PP nanocomposites with either polyethylene octene elastomer grafted maleic anhydride (POEgMAH) or PP grafted maleic anhydride (PPgMAH) as compatibilizer were prepared using co-rotating twin-screw extruder followed by injection molding. The mechanical and microstructural properties of the composites were investigated by means of tensile, flexural, and impact testing and by scanning electron microscopy (SEM). X-ray diffraction (XRD) was used to characterize the formation of nanocomposites. The result indicated that the miscibility of PA6/PP nanocomposites was improved with the addition of POEgMAH and PPgMAH. The impact strength of PA6/PP nanocomposite with POEgMAH increased about 5 times higher than uncompatibilized composite. Increment in tensile properties was observed when PPgMAH was used as compatibilizer. XRD results revealed that PA6/PP nanocomposites were successfully formed. Uniform dispersion of PP in matrix were observed through SEM, which showed the improvement of the compatibility between polymers.